The Incidence and Risk Factors for Lower Limb Skin Graft Failure - Sumeet Reddy; Falah El-Haddawi; Michael Fancourt; Glenn Farrant; William Gilkison; Nigel Henderson; Stephen Kyle; Damien Mosquera (Dermatology Research and Practice)
Lower limb skin grafts are thought to have higher failure rates than skin grafts in other sites of the body. Currently, there is a paucity of literature on specific factors associated with lower limb skin graft failure. We present a series of 70 lower limb skin grafts in 50 patients with outcomes at 6 weeks. One-third of lower limb skin grafts went on to fail with increased BMI, peripheral vascular disease, and immunosuppressant medication use identified as significant risk factors.